Principles of parallel programming. - Lin, Calvin, ....-; Snyder, Lawrence, 1946- (Boston : Pearson, 2009)
Written by top researchers Larry Snyder and Calvin Lin, this highly anticipated first edition emphasizes the principles underlying parallel computation, explains the various phenomena, and clarifies why these phenomena represent opportunities or barriers to successful parallel programming.Introduction: Parallelism = Opportunities + Challenges; Introduction: Parallelism = Opportunities + Challenges; Reasoning about Performance; First Steps Towards Parallel Programming; Scalable Algorithmic Techniques; Programming with Threads; Local View Programming Languages; Global View Programming Languages; Assessing Our Knowledge; Future Directions in Parallel Programming; Capstone Project: Designing a Parallel Program.For all readers (particularly software engineers and computer system designers) interested in multi-core architecture and parallel programming.